Environmental management system ISO 14001: Effective waste minimisation in small and medium enterprises in India - Singh, Mitrabinda; Brueckner, Martin; Padhy, P. (Elsevier, 2015)
Numerous empirical and conceptual studies describe waste minimisation as a key environmental performance indicator for industry. ISO 14001certification in this regard is widely considered the tool of choice for driving waste minimisation efforts. To this day, however, the evidence remains mixed as it pertains to the effectiveness of ISO 14001 in helping firms reduce waste, especially in developing countries. This paper explores the waste minimisation efforts among Indian small and medium enterprises. Specifically, improvements in waste minimisation are analysed from small and medium enterprises operating in the cities of Delhi and Noida. Our proposed model is tested for a model-fit, and the hypotheses are tested through regression coefficient (ß) scores to determine the influence of ISO 14001 on the degree of waste minimisation among certified and non-certified companies. The data reveal that ISO 14001 certification alone helped account for a 25% increase in waste minimisation in certified companies after controlling for other critical factors (correlated to the variable 'waste minimisation') that may influence this relationship. The analytical tools described in this paper lend themselves to be applied to similar research problems in future studies. The study provides baseline data for further research into ISO 14001 effectiveness in the Indian SME context - a field with still only limited research insights - and offers policy prompts for targeted environmental management improvements in Indian firms.